Daftar Cek Masalah sebagai Asesmen Kebutuhan Siswa si Sekolah Menengah - Habsy, Bakhrudin All; Puspitahaqni, Vivi; Berliana, Aulia Risa (TSAQOFAH, 2024)
A problem checklist is a tool used to identify problems or difficulties faced by individuals. This research aims to assess the needs of secondary school students regarding problem checklists in the context of understanding and solving problems. The literature review method is used to collect information from relevant sources. The results of the literature review show that problem checklists can be an effective tool in helping students identify problems, understand their root causes, and find appropriate solutions. This article provides valuable insight into developing a more holistic approach to integrating problem checklists in secondary school curricula to improve students' problem-solving skills. The results of this research include the implementation of a problem checklist which can help improve communication and coordination between school staff, parents, and students. By using a problem checklist, all parties can have a clear understanding of the problems that need to be resolved as well as the actions taken to resolve these problems.